2008
DOI: 10.1177/0888406408330632
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Modeling Collaborative Teaching for Pre-Service Teachers

Abstract: In this article, the authors examine pre-service special education teacher reaction to and experience in a collaboratively taught higher education course. Forty-three full-time postbaccalaureate students participate in a course designed to examine critical issues in special education, taught by two faculty members, one specializing in mild and moderate disabilities and the other in moderate and severe disabilities. Pre-service teachers respond to a survey about their knowledge and comfort with co-teaching. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Without question, teachers need opportunities to observe collaboration, attempt the act of coteaching in practice, and receive feedback on their efforts during training (Brownell, Ross, Colón, & McCallum, 2005;Stang & Lyons, 2008). In many cases, however, teachers are left to improve co-teaching practices on their own (Kamens, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Without question, teachers need opportunities to observe collaboration, attempt the act of coteaching in practice, and receive feedback on their efforts during training (Brownell, Ross, Colón, & McCallum, 2005;Stang & Lyons, 2008). In many cases, however, teachers are left to improve co-teaching practices on their own (Kamens, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Further, in co-teaching relationships in a mentorship context, mentor-teachers and teacher-candidates face a power imbalance; one is experienced and responsible to evaluate the other. Thus, not only do these pairs find parity elusive (Stang & Lyons, 2008), but also candidates endeavor to be seen as "real" teachers (Bacharach et al, 2010).…”
Section: The Relational Nature Of Co-teaching and Collaborationmentioning
confidence: 99%
“…Harris and Harvey (2000) recommended that co-teaching in higher education create opportunities for modeling different approaches to teaching, as well as how to respond to tensions and conflict that may arise in the classroom. From their research of pre-service teachers, Stang and Lyons (2008) found that all students in their study acknowledged the value to learning through observing co-teaching. Further, Plank (2011) argued that students observing "their teachers learn from each other and even disagree with each other models for students how scholars and informed citizens within a community of learning can navigate a complex and uncertain world" (p. 5).…”
Section: Rationale For Co-teaching In Higher Educationmentioning
confidence: 99%